Development of Kinetic Models For Biogas Production From Tofu Liquid Waste - Lukhi Mulia Shitophyta; Anisa Salsabila; Firanita Anggraini; Siti Jamilatun (Faculty of Science and Technology Universitas Islam Negeri Ar-Raniry, 2021)
Abstract: Biogas promises bioenergy to be developed as a renewable fuel to reduce the fossil energy crisis. Biogas raw material can be derived from tofu liquid waste. Biogas is processed by anaerobic digestion. This study aimed to develop a simulation of the kinetic model variations of biogas production from tofu liquid waste. The results showed that the ascending limb of the exponential equation had a greater coefficient (R2 = 1) than the ascending limb of the linear equation (R2 = 0.9574). The descending limb of the linear equation had a better coefficient (R2 = 0.9574) than the descending limb of the exponential equation (R2 = 0.95). The Gaussian model had the greatest R2 of 0.9937. Logistic growth had the greatest coefficient (R2 = 0.9951) compared to modified Gompertz (R2 = 0.9817) and exponential rise to maximum (R2 = 0.9852) in the simulation of cumulative biogas production. The fit model for kinetic biogas production from tofu liquid waste is Gaussian Model.Abstrak: Biogas merupakan salah satu bioenergi yang menjanjikan untuk dikembangkan dalam mengurangi krisis energi fosil. Bahan baku biogas dapat berasal dari limbah cair tahu yang diolah secara anaerobic digestion. Penelitian ini bertujuan untuk mengembangkan variasi model simulasi kinetika produksi biogas dari limbah cair tahu. Hasil penelitian menunjukkan bahwa persamaan eksponensial untuk grafik kenaikan memilki koefisien yang lebih besar (R2 = 1) dibandingkan grafik kenaikan dengan persamaan linier (R2 = 0,9574). Grafik penurunan pada persamaan linier memiliki nilai koefisien lebih besar (R2 = 0,9574) dibandingkan grafik penurunan pada persamaan eksponensial (R2 = 0,95). Model Gaussian menghasilkan nilai koefisien tertinggi R2 = 0,9937. Logistic growth menghasilkan nilai R2 terbesar (0,9951) dibandingkan modified Gompertz (R2 = 0,9817) dan exponential rise to maximum (R2 = 0,9852) pada simulasi produksi biogas kumulatif. Model yang paling cocok untuk kinetika produksi biogas dari limbah cair adalah model Gaussian.